Grlom u jagode (Epizoda 5) - One stvari . With a Throat into Strawberries (Episode 5) - Those Things - Karanović, Srđan (RTV Beograd, 1975)
The fifth episode introduces a new major character of the series: easygoing Tale who becomes Bane’s sister's new boyfriend and immediately brings new light into the life of the whole family. He also happens to play a major role in Bane’s sexual upbringing as Bane suddenly finds himself pressured by everyone around him to finally “become a man” in yet another respect. A chance appears when Bane and his new girlfriend plan a romantic trip on the night train. However, once again something goes wrong and Bane loses his virginity under much less romantic circumstances and with major help from Tale.